Egypt’s deserts – geotourist attraction - Plit, Joanna (Geotourism/Geoturystyka)
In Egypt we can find all the classic desert landscapes: clayey, sand, gravell deserts and rocks hammadas. Here and there occurs oasis shaded with the palms and alkali shotts, dry wadi and shifting sward dunes. Diversity of relief and geology of different types of the deserts determined the variety of hydrography, specific plant cover and vegetation of Sahara’s severity of the subtropical climate. Admiration of the various kinds of deserts is possible during the trip along the range of the New Valley paralleled to the Nile River Valley. The following oasis are worth to be seen: El Charga, Mut, Balat, Dahla, El Qasr Farafra, El Heim Bahariya and Siwa.